Perioperative red blood cell transfusion and mortality following heart transplantation: A retrospective nationwide population‐based study between 2007 and 2016 in Korea. Issue 10 (3rd July 2019) - Nam, Karam; Jang, Eun Jin; Kim, Ga Hee; Yhim, Hyung Been; Lee, Hannah; Kim, Dal Ho; Ryu, Ho Geol
Abstract: Background: Patients undergoing heart transplantation (HT) frequently receive perioperative red blood cell (RBC) transfusions, but the impact of perioperative transfusion on clinical outcomes after HT remains unclear. Methods: All adult HTs performed in Korea between 2007 and 2016 were analyzed using data from the National Health Insurance Service. Patients were classified into four groups based on the number of RBC units transfused during hospital admission for HT: 0, 1 to 2, 3 to 5, and greater than or equal to 6 units. In‐hospital and long‐term mortality rates were compared among the groups. Results: In total, 833 adults HTs were included in the study. The overall in‐hospital mortality rate was 8.4% (70 of 833), with no mortality occurring in patients who received no transfusion. The in‐hospital mortality rate was higher in patients requiring  greater than or equal to 6 units (25.1%) than in patients who received 1 to 2 units (0.3%) and 3 to 5 units (2.7%; P  < .001). Patients who received   greater than or equal to 6 units of RBCs had a significantly higher risk of all‐cause mortality after HT compared to patients who received no transfusion (hazard ratio [95% confidence interval], 5.99 [1.46‐24.56]; P  = .012). Long‐term survival rate was also lower in patients who received transfusions of greater than or equal to 6 units of RBCs than in patients who received no transfusion ( P  < .001). Conclusions: Perioperative transfusion of greater than or equal to 6 units of RBCs may be associated with an increased risk of in‐hospital and long‐term mortality after HT.